EFFECT OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE THROUGH WORKING DISCIPLINE AT PT. BAMBOO TIRTA ENGINEERING - Munawaroh; Suharto; Dr. Iwan Kurniawan Subagja (The Institute of Academic Research and Publication (IARP), 2020)
This study aims to: 1) To determine and analyze the effect of motivation and job satisfaction on work discipline, 2) To determine and analyze the effect of motivation and job satisfaction on employee performance, 3) To determine and analyze the effect of work discipline on employee performance, 4) To find out and analyze the influence of motivation and job satisfaction on employee performance through work discipline PT. Bambu Tirta Engineering. The research was conducted at PT. Bambu Tirta Engineering with a research sample of 64 respondents. The sampling technique uses saturated samples. Methods of data analysis using descriptive analysis and quantitative analysis with path analysis. The results showed that: 1) there is an effect of motivation and job satisfaction on work discipline, 2) there is an effect of motivation and job satisfaction on employee performance, 3) there is an effect of work discipline on the performance of employees of PT. Bambu Tirta Engineering and 4) there is no influence between motivation and job satisfaction on employee performance through work discipline PT. Bambu Tirta Engineering. This means that the direct effect is greater than the indirect effect, the work discipline variable cannot mediate between motivation and job satisfaction on employee performance at PT. Bambu Tirta Engineering.